Assessing the comparative efficacy of multiple whole-blood count-based testing strategies for thalassaemia diagnosis: A meta-analysis - Samanta, Abhishek; Bhattacharyya, Nandan (Asian journal of pharmaceutical research and health care, 2023)
Context: Complete blood count (CBC) with confirmatory high-performance liquid chromatography (HPLC) is the gold standard for thalassemia screening. Because of the constraints of a high-pressure liquid chromatography facility, they develop alternative approaches to screening when the population to be screened is large. Aims: The objective of this meta-analysis is to evaluate the diagnostic accuracy of alternative approaches to thalassemia screening. This study is important, as accurate and accessible thalassemia screening can improve the quality of life for patients and reduce the burden on health-care systems. Settings and Design: The systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Subjects and Methods: The present systematic review comprises 74,284 thalassemia-positive patients, identified using CBC and conventional HPLC methods was published between 2012 and 2022. After further screening, 23 studies were included in the present study. Statistical Analysis Used: The Moses-Littenberg Summary Receiver Operating Characteristic (SROC) model, the bivariate model, and the SROC reporting model are the examples of models that also consider sensitivity and specificity. Results: The total diagnostic odds ratio was 88.981 (95% confidence interval 37.645-210.321). Subgroup analysis was determined by a mixed-effects model, with I2 (residual heterogeneity/unaccounted variability) at 90% and Partial Area under ROC curve (restricted to observed False Positive Rates and normalized) was 0.951. Conclusions: This systematic review investigated the efficacy of using CBC parameters to distinguish between iron deficiency anemia and the thalassemia trait. This can help reduce health-care costs and improve the accuracy of the results.